Ecological and taxonomic diversity of nematode communities in soils of the Zarafshan Valley (Uzbekistan) and its edaphic determinants - DILNOZA M. NURMATOVA; SARDORBEK B. NARZULLAYEV; OCHIL MAVLYANOV; UKTAM N. MIRZAEV; RUSTAM SH. URALOV; SHAHLO SH. TURSUNOVA; FERUZ A. SHODMONOV; JAKHONGIR E. OBLOKULOV; SARDORBEK S. KAMBAROV; INTIZOR R. AVAZMETOVA; KHULKAR SH. URINOVA; DILFUZA SH. YODGOROVA (Society for Indonesian Biodiversity, 2026)
Abstract. Nurmatova DM, Narzullayev SB, Mavlyanov O, Mirzaev UN, Uralov RS, Tursunova SS, Shodmonov FA, Oblokulov JE, Kambarov SS, Avazmetova IR, Urinova KS, Yodgorova DS. 2026. Ecological and taxonomic diversity of nematode communities in soils of the Zarafshan Valley (Uzbekistan) and its edaphic determinants. Biodiversitas 27 (2): d270203. https://doi.org/10.13057/biodiv/d270203. Soil nematodes are key bioindicators of belowground ecosystem functioning and soil health. This study analyzed the trophic and taxonomic structure of nematode communities in apple orchards of the Zarafshan Valley (Uzbekistan) and assessed their relationships with soil physicochemical properties. The study, conducted from 2023 to 2025, investigated the nematode diversity associated with intensive apple orchards in depth, in relation to soil factors. A total of 240 samples were collected from 8 apple orchards using the route method in spring, summer, and fall. The samples were processed using the modified Berman’s funnel method and flotation method. A total of 1277 individuals representing 54 nematode species, 25 genera, and four orders were identified from root and soil samples collected at 0-20 and 20-40 cm depths. The highest diversity of species and individuals was observed in the top layer of soil. This layer contained 90% of the species and 59% of the individuals of the fauna. The dominant ecological groups were omnivores-predators (Dorylaimus, Eudorylaimus), bacterivores (Cephalobus, Panagrolaimus), and plant parasites (Pratylenchus, Helicotylenchus). Species richness and abundance were markedly higher in the upper soil layer, which contained more humus, nitrogen, and phosphorus, and had lower bulk density. Principal Component Analysis (PCA) revealed that humus, N, P, pH, and K were the main environmental determinants shaping nematode community composition. According to PCA analysis, bacterivores and omnivores had positive correlations with humus and N, while plant parasites were mainly associated with high P and K concentrations. These findings highlight the ecological sensitivity of nematode trophic groups to soil fertility gradients and physicochemical conditions. By studying the taxonomic and ecological diversity of nematodes, revealing their degree of association with soil factors, it is possible to improve intervention strategies to maintain soil health and stability in semi-arid horticultural ecosystems.